KEAMANAN DALAM TINDAKAN ANESTESIA - Sakliressy, Magdalena F; Kumaat, Lucky T; Wuwungan, Antje A (JURNAL BIOMEDIK : JBM, 2012)
Abstract: In general, anaesthetic means an act of relieving pain during surgery and or other procedures that cause pain in the body. In all anaesthetic procedures safety is of most concern, including the reduction of any risks of danger or related complications that can happen during anaesthesia. Understanding about the stages of anasthesia from pre-anesthesia until post-anasthesia, as well as techniques of anasthesia, is very important in creating the anaesthesia safety.Key words: safety, anaesthetic, anaesthesia, patientAbstrak: Secara umum, anestesia berarti suatu tindakan menghilangkan rasa nyeri saat melakukan pembedahan dan atau berbagai prosedur lainnya yang menimbulkan rasa nyeri pada tubuh. Dalam setiap tindakan anestesia harus diperhatikan segi keamanannya. Pemahaman mengenai tahap-tahap anaestesia sejak pre anestesia sampai dengan pasca anestesia serta tehnik-tehnik anestesia sangat diperlukan untuk mencapai keamanan dalam tindakan anestesiaKata Kunci: keamanan, tindakan, anestesia, pasien